1999
DOI: 10.1063/1.370666
|View full text |Cite
|
Sign up to set email alerts
|

Electron inelastic interactions with overlayer systems

Abstract: An overlayer system composed of a thin film on the top of a semi-infinite substrate was studied in this work for electron inelastic interactions. Analytical expressions for the depth-dependent inelastic differential and integral inverse mean free paths were derived for both incident and escaping electrons. The interface ͑film-substrate͒ effect and the surface ͑vacuum-film͒ effect were analyzed by comparing the results of an overlayer system and a semi-infinite system. It was found that the interface effect ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
(2 reference statements)
1
17
0
Order By: Relevance
“…To the best of our knowledge, no detailed discussion of the implications or the effect of this approximation exists in the literature. Moreover, several later models use this approximation with the sole justification of a reference to the aforementioned work or to works which in turn make a reference to it. Another approximation that is made in some works (sometimes tacitly) consists in replacing q by q ‖ in the last bracket in Eqn .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no detailed discussion of the implications or the effect of this approximation exists in the literature. Moreover, several later models use this approximation with the sole justification of a reference to the aforementioned work or to works which in turn make a reference to it. Another approximation that is made in some works (sometimes tacitly) consists in replacing q by q ‖ in the last bracket in Eqn .…”
Section: Resultsmentioning
confidence: 99%
“…By choosing appropriate values for ( p 1 , p 2 , p 3 ), e.g. (0,1,0) for the Chen and Kwei model, and introducing further approximations as required, it is in principle possible to reproduce most of the subset of semiclassical models for surface excitations found in the literature . As pointed above, the model of Yubero and Tougaard is not suited for comparison within the presented framework, for it takes a different approach.…”
Section: Resultsmentioning
confidence: 99%
“…Chen and Kwei derived a semi-classical expression for DIIMFP including the depth-dependence of surface excitation and found that the surface excitation effect was extended to both sides of the solid surface [9]. Intensity of electrons backscattered from solid surfaces [10] and from a binary compound [11], were calculated using a MC algorithm applying these depth dependent DIIMFP calculations and the straight line approximation in the surface region. A theoretical derivation of the DIIMFP for electrons moving across the solid surface was given by Li et al [1] on the basis of the dielectric response theory and the extended Drude dielectric functions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] For the charged particle moving parallel to a semi-infinite solid, theoretical approaches [7][8][9] were proposed to calculate the induced potentials which resulted in surface plasmon excitations, i.e., collective oscillations of the quasifree electrons near the surface. Much attention has been paid to the inelastic interaction cross sections between the charged particle and the solid surface.…”
Section: Introductionmentioning
confidence: 99%